Performance Appraisal System and Employee Motivation in International Non-Governmental Organizations in Nepal - Biswakarma, Gangaram; Kadayat, Sanjog Singh (Journal of Business and Management, 2023)
Background: Strong organizations must maintain vital activities and help others survive. All non-profit organizations (NPOs) aim to increase customers’ social well-being. These organizations have been under pressure to enhance management, efficiency, effectiveness, and accountability recently. A performance evaluation system is essential to internal monitoring and control in non-governmental organizations due to a diversified and linked workforce that works toward several layers of organization-specified objectives at different levels. Objectives: This study aims to explore the performance appraisal system of International Non-Governmental Organizations in Nepal. Additionally, it is to analyze the effect of the performance appraisal system on employee motivation in these organizations in Nepal. Methods: The study adopted a mix-method. Data were collected using a structured questionnaire of 300 employees, with 212 responses from six INGOs operating in Nepal and 5 HR managers of the INGOs. The performance appraisal system considered components, i.e., performance appraisal purpose, performance appraisal standard, feedback on performance appraisal, reliability of ratings, and rather assurance on employee motivation. Findings: The results determined that performance appraisal purpose, reliability of ratings, and rater assurance significantly affect employee motivation. In contrast, feedback on performance appraisal and performance appraisal standards did not significantly impact employee motivation. Conclusions: An organization’s fair and accurate performance appraisal system helps employees feel unbiased and motivates them toward work. Employees should receive performance appraisals to verify that the authorities have reviewed their work. It inspires them.